SCT Tree Model to Integrate Spirituality and Computational Thinking in Science Learning - Suwardi; Hariyadi, Rahmat; Susapti, Peni; Billah, Arif; Kurniawan, Wawan; Ari Prabowo, Sigit (Universitas Negeri Semarang, 2025)
The integration of spiritual values and Computational Thinking (CT) in science learning at Madrasah Ibtidaiyah remains limited and has not been systematically addressed. This study aims to develop the SCT Tree Model, an innovative instructional model that integrates spirituality with CT in science learning, and to examine its effectiveness on students’ learning outcomes at Madrasah Ibtidaiyah. This study employed a mixed-methods approach with a sequential exploratory design, involving six experts, 241 teachers, and 188 students across Central Java, Indonesia. The model was validated by experts and practitioners, showing a valid category (Aiken’s V = 0.81–0.93). A pilot test indicated an increase in average scores from 79 to 94 (+15 points), while a large-scale trial demonstrated an increase from 72 to 90 (+18 points). Experimental testing across three regions confirmed that the SCT Tree Model contributed 84.5% to students’ science learning outcomes, with significant differences compared to conventional instruction. The novelty of this research lies in the systematic integration of spiritual values and CT through seven contextually based tree syntaxes. Practically, the model offers a concrete solution for Madrasah Ibtidaiyah teachers to implement holistic science learning that aligns with national curriculum policies and 21st-century educational demands.